THE EFFECT OF USING EDUCATIONAL TIKTOK VIDEOS AS A MEDIUM FOR LEARNING ENGLISH VOCABULARY AT MTS QARYATUL JIHAD BENGKULU TENGAH (A Quasi-Experimental Research at Seventh-Grade Students). - Putri Muharani, Marsanda; Nadrah; Serasi, Reko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocabulary mastery is a core element of English language learning, playing a crucial role in supporting speaking, listening, reading, and writing skills. However, English vocabulary among junior high school students in Indonesia remains relatively limited, partly due to conventional teaching methods that fail to actively engage students. This study aims to examine the impact of TikTok educational videos on the English vocabulary mastery of seventh-grade students at MTs Qaryatul Jihad, Central Bengkulu. This research adopted a quantitative approach using a quasi-experimental design (non-equivalent control group design). The sample comprised 36 students, consisting of 18 students from Class VII A as the experimental group and 18 students from Class VII B as the control group. Data were gathered through pre-tests and post-tests in the form of multiple-choice tests containing 37 valid items, which were then analyzed using the Independent Sampes t-test and ANCOVA with SPSS version 26. The findings revealed that the use of TikTok educational videos had a significant impact on students' vocabulary mastery. The Independent Samples t-test produced a significance value of 0.000 (p < 0.05), leading to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (H₀). Furthermore, the ANCOVA results confirmed that TikTok educational videos influenced students' vocabulary mastery, with a Partial Eta Squared value of 0.446. These findings indicate that TikTok educational videos serve as an effective learning medium for enhancing students' English vocabulary mastery.